Designing Procurement Strategies for Greater SC Resilience - Kramar, Uroš (Strenghtening Supply Chains: Strategies for Resilience and Agility, 2026)
Disruption in modern supply chains is inevitable, so increasing the resilience of organizations is crucial. Strategic procurement, especially through the Kraljic matrix, is key to greater resilience. This model classifies procurement sources into four main groups: strategic, leveraged, bottlenecks and non-critical products, each of which requires a specific approach. It should be understood that the factors affecting the rating in this matrix are not always equally important and have different values. Designing procurement strategies based on this matrix is a complex dynamic process that enables organizations to better adapt to changing conditions and needs. The Kraljic matrix is a valuable tool for managing disruptions in supply chains, as it helps organizations increase resilience and stability. Procurement strategies based on this model are an effective approach for successful operations in an unpredictable business environment.